Raman exfoliative cytology for prognosis prediction in oral cancers: A proof of concept study. Issue 8 (24th April 2019) - Sahu, Aditi; Gera, Poonam; Malik, Akshat; Nair, Sudhir; Chaturvedi, Pankaj; Murali Krishna, C.
Abstract : Oral cancer is associated with high rates of recurrence, attributable to field cancerization. Early detection of advanced field changes that can potentially progress to carcinoma can facilitate timely intervention and can lead to improved prognosis. Previous in vivo studies have successfully detected advanced field effects in oral cancers. Raman exfoliative cytology has previously shown to differentiate normal, oral pre‐cancer and cancers. The present study explores Raman‐exfoliative‐cytology‐based detection of field effects. Exfoliated cells were collected from tumor (n = 16) and contralateral‐normal appearing mucosa (n = 16) of oral cancer patients, and healthy tobacco habitués (n = 20). After spectral acquisition, specimens were Pap‐stained for cytological evaluation. Data analysis, by Principal Component Analysis and Principal Component‐Linear Discriminant Analysis, indicate several spectral‐misclassifications between contralateral normal and tumor, which were investigated and correlated with spectral, cytological and clinical outcomes. A qualitative analysis by grouping patients with number of misclassifications with tumor (Group 1: 0, Group 2: 1 and Group 3: >1) was explored. Group 3 with highest misclassifications showed spectral and cytological similarity to tumor group — one patient was a case of early inoperable residual disease, despite clear margins on histopathology. Thus, these misclassifications could be indicative of cancer field changes, and can prospectively help to identify patients susceptible to recurrences . Abstract : Oral cancer is associated with high rates of recurrence attributable to field cancerization. Early detection of advanced field changes that can potentially progress to carcinoma can facilitate timely intervention and can lead to improved prognosis. The present study explores Raman‐exfoliative‐cytology‐based detection of field effects and can prospectively help identify patients susceptible to recurrences.